Financial Stability of Indonesia’s Islamic Banks: Analysis Profitability - Rahmat Kurnia; Hilmy Baroroh; Riska Fauziah Hayati; Haura Hazimah Melzatia; Rakotoarisoa Maminirina Fenitra (EKONOMIKA SYARIAH : Journal of Economic Studies, 2024)
The study explores the financial well-being of Islamic banks in Indonesia, focusing on profitability as reflected in the Return on Assets (ROA) ratio. This article brings attention to the issue of certain Sharia Commercial Banks in Indonesia exhibiting poor financial conditions, as indicated by low ROA figures. The primary aim of the research is to evaluate the impact of Good Corporate Governance (GCG), Non-Performing Financing (NPF), and the ratio of Operational Costs to Operational Income (BOPO) on the financial sustainability of these banks. This research adopts a quantitative approach, utilizing secondary data sourced from financial and Good Corporate Governance reports spanning the years 2018 to 2022. The analysis is conducted using panel data regression with the aid of EViews 12 software. The study covers 11 Sharia Commercial Banks in Indonesia over a five-year period, resulting in a sample of 55 observations obtained through purposive sampling. The findings indicate that Good Corporate Governance and Non-Performing Financing significantly influence the Return on Assets, underscoring the critical role these factors play in maintaining financial stability. In contrast, the BOPO ratio does not exert a significant effect on ROA. Furthermore, the results of the simultaneous regression analysis confirm that GCG, NPF, and BOPO collectively have a meaningful impact on the financial performance of Islamic banks, as measured by ROA. Penelitian ini mengeksplorasi kesehatan finansial bank syariah di Indonesia, dengan penekanan pada profitabilitas yang diukur melalui rasio Return on Assets (ROA). Artikel ini menyoroti permasalahan beberapa Bank Umum Syariah di Indonesia yang menunjukkan kondisi keuangan yang kurang baik, yang tercermin dalam rendahnya angka Return on Assets (ROA). Penelitian ini bertujuan untuk menilai pengaruh Good Corporate Governance (GCG), Non-Performing Financing (NPF), dan rasio Biaya Operasional terhadap Pendapatan Operasional (BOPO) terhadap keberlanjutan keuangan bank-bank ini. Pendekatan penelitian ini bersifat kuantitatif, dengan menggunakan data sekunder yang diperoleh dari laporan keuangan dan laporan Good Corporate Governance dalam rentang waktu 2018 hingga 2022. Analisis dilakukan menggunakan regresi data panel dengan bantuan perangkat lunak EViews 12. Penelitian ini melibatkan 11 Bank Umum Syariah di Indonesia selama lima tahun, dengan total 55 observasi yang diperoleh melalui teknik purposive sampling. Hasil penelitian menunjukkan bahwa Good Corporate Governance dan Non-Performing Financing memiliki pengaruh signifikan terhadap Return on Assets, yang menggarisbawahi pentingnya kedua faktor tersebut dalam mempertahankan stabilitas keuangan. Sebaliknya, rasio BOPO tidak menunjukkan dampak yang signifikan terhadap ROA. Selain itu, hasil analisis regresi simultan mengukuhkan bahwa GCG, NPF, dan BOPO secara bersama-sama memberikan pengaruh yang berarti terhadap kinerja keuangan bank syariah, yang diukur melalui ROA.